Tomographic Images of Klyuchevskoy Volcano P-Wave Velocity - Lees J.; Symons N.; Chubarova O.; Gorelchik V.; Ozerov A. (American Geophysical Union, 2007)
Three-dimensional structural images of the P-wave velocity below the edifice of the great Klyuchevskoy group of volcanoes in central Kamchatka are derived via tomographic inversion. The structures show a distinct low velocity feature extending from around 20 km depth to 35 km depth, indicating evidence of magma ponding near the Moho discontinuity. The extensive low velocity feature represents, at least to some degree, the source of the large volume of magma currently erupting at the surface near the Klyuchevskoy group.
Keywords: 38.01.77 Методы исследования и моделирования. Математические и кибернетические методы в геологии; 38.37.25 Вулканология; Ключевской